Values System in fifth-year high school of Lima from different socioeconomic levels - Escurra Mayaute, Luis Miguel (2003)
It was studied the structure of the values system of senior high schools students belonging to different socio-economic levels using Schwartz Theory as a framework. The participants were 1197 students sampled on a stratified probabilistic way, belonging to all school districts (USES) of Lima, Peru. The results of the psychometric analysis allowed to obtain the validity content index, the construct validity and the reliability index of the Schwartz Values Questionnaire (PVQ). The results showed that the scores of the students of the PVQ reached a normal distribution. The comparative analysis of the socioeconomic levels indicated that values of tradition and security prevail in low socio-economic students. The value of power prevails in students of middle socioeconomic level and the benevolence value prevails in the high socio-economic level. The values of self direccion, hedonism and achievement prevail at the high and middle social economic levels. The comparison for sex allowed to observe that values as benevolence, universalism and security prevail in women and values of achievement and power prevail in males. Finally it was found three kind of profiles acoord to the form of responding to the PVQ.